Advanced mono‐ and multi‐dimensional gas chromatography–mass spectrometry techniques for oxygen‐containing compound characterization in biomass and biofuel samples. Issue 1 (9th December 2020) - Beccaria, Marco; Siqueira, Anna Luiza Mendes; Maniquet, Adrien; Giusti, Pierre; Piparo, Marco; Stefanuto, Pierre‐Hugues; Focant, Jean‐François
Abstract: A wide variety of biomass, from triglycerides to lignocellulosic‐based feedstock, are among promising candidates to possibly fulfill requirements as a substitute for crude oils as primary sources of chemical energy feedstock. During the feedstock processing carried out to increase the H:C ratio of the products, heteroatom‐containing compounds can promote corrosion, thus limiting and/or deactivating catalytic processes needed to transform the biomass into fuel. The use of advanced gas chromatography techniques, in particular multi‐dimensional gas chromatography, both heart‐cutting and comprehensive coupled to mass spectrometry, has been widely exploited in the field of petroleomics over the past 30 years and has also been successfully applied to the characterization of volatile and semi‐volatile compounds during the processing of biomass feedstock. This review intends to describe advanced gas chromatography–mass spectrometry‐based techniques, mainly focusing in the period 2011–early 2020. Particular emphasis has been devoted to the multi‐dimensional gas chromatography–mass spectrometry techniques, for the isolation and characterization of the oxygen‐containing compounds in biomass feedstock. Within this context, the most recent advances to sample preparation, derivatization, as well as gas chromatography instrumentation, mass spectrometry ionization, identification, and data handling in the biomass industry, are described.